Relationship between Shear Velocities Recorded by Microtremor Observations and Seismic Cone Penetration Test Results - Rusnardi Rahmat Putra; J. Kiyono; Sai K. Vanapalli; Y. Ono (Indonesian Journal of Science and Technology, 2021)
This research proposes a relationship between two methods such as a numerical approach by conducting a microtremor array observation and field survey by using the seismic cone penetration test unit (SCPTu). A database of shear-wave velocity (Vs) measurements was established using the microtremor array technique and seismic cone penetration test unit (SCPTu) on high-quality samples of rock and soft soil in Padang city, Indonesia. The study also demonstrates that the Vs values obtained from the different methods are consistent with the microtremor array technique. This technique may thus be deemed a valuable tool, as it can be used in engineering practice with confidence. Comparison of the Vs for different soils at the first layer between the microtremor array observation results and the SCPTu results exhibited the microtremor array method is unable to determine the Vs  at the layer where its Vs changes dramatically, such as at the same layer as station UNP at 2 to 3.5m deep.